2008
DOI: 10.1152/ajpcell.00224.2008
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal sarcoplasmic reticulum Ca2+-sequestering properties in skeletal muscle in chronic obstructive pulmonary disease

Abstract: concentration for 10 -90% Vmax). For the sarco(endo)plasmic reticulum Ca 2ϩ -ATPase (SERCA) isoforms, SERCA1a was 16% higher (P Ͻ 0.05) and SERCA2a was 14% lower (P Ͻ 0.05) in COPD. It is concluded that moderate to severe COPD results in abnormalities in SR Ca 2ϩ -ATPase properties that cannot be explained by changes in the SERCA isoform phenotypes. The reduced catalytic properties of SERCA in COPD suggest a disturbance in Ca 2ϩ cycling, possibly resulting in impairment in Ca 2ϩ -mediated mechanical function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 53 publications
1
21
1
Order By: Relevance
“…-ATPase measured microphometrically in the different fiber types. Unlike our finding in which we have reported reductions in the maximal catalytic activity in COPD when measured in whole muscle homogenates (Green et al 2008c), differences in the weighted Ca 2? -ATPase were not found when assessed histochemically.…”
Section: Discussioncontrasting
confidence: 99%
“…-ATPase measured microphometrically in the different fiber types. Unlike our finding in which we have reported reductions in the maximal catalytic activity in COPD when measured in whole muscle homogenates (Green et al 2008c), differences in the weighted Ca 2? -ATPase were not found when assessed histochemically.…”
Section: Discussioncontrasting
confidence: 99%
“…Whether skeletal muscle SERCA levels and activity are also diminished has not been studied. Interestingly, in the skeletal muscle of patients with COPD, another chronic disease characterized by skeletal myopathy, SERCA activity was indeed found to be reduced, and calcium uptake was found to be slower compared to controls (24). These investigators postulated that the presence of reactive oxygen species (ROS) in skeletal muscle in COPD may lead to SERCA damage and dysfunction.…”
Section: What Are the Salient Features Of The “Skeletal Myopathy” Of mentioning
confidence: 99%
“…ROS–mediated damage to SERCA has been hypothesized as another potential mechanism of diminished calcium sequestration following calcium release from the SR. Other hyperadrenergic states, including COPD, also manifest this altered calcium cycling, leading to similar impairment of skeletal muscle function (24). …”
Section: What Are the Salient Features Of The “Skeletal Myopathy” Of mentioning
confidence: 99%
“…Interestingly, although the high cost of SR Ca 2ϩ pumping during exercise is often not appreciated, SERCA dysfunction (i.e., slowing in the Ca 2ϩ uptake after contractions) has been implicated in many pathological states, including chronic obstructive pulmonary disease (13), muscular dystrophy (11), and heart failure (19). Because SERCA dysfunction may be an important factor associated with the decreased locomotor activity in these diseases (13), the study of the factors that influence SERCA activity during fatigue is very relevant.…”
mentioning
confidence: 99%
“…Because SERCA dysfunction may be an important factor associated with the decreased locomotor activity in these diseases (13), the study of the factors that influence SERCA activity during fatigue is very relevant.…”
mentioning
confidence: 99%